2015
DOI: 10.1111/jpn.12408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary Lactobacillus acidophilus and Bacillus subtilis on laying performance, egg quality, blood biochemistry and immune response of organic laying hens

Abstract: The objective of this study was to evaluate the effects of two different probiotic micro-organisms on the performance, egg quality and blood parameters of organically reared hens. A total of 900 16-week-old Hy-Line layer hybrids were randomly assigned to three groups of 300 birds each. The control (CTR) group was fed a corn-soya bean cake-based diet; the L group was fed the same diet supplemented with 0.1% Lactobacillus acidophilus, while the B group was fed the same diet supplemented with 0.05% Bacillus subti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 53 publications
5
27
1
3
Order By: Relevance
“…The present study compared the effects of LO, NFA, and FA supplementation in layer diets. No significant differences in laying performance and egg quality were found by LO addition compared with the CON group, which is consistent with a previous study (Forte et al, 2016). The dietary inclusion of NFA and FA significantly increased the egg weight.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study compared the effects of LO, NFA, and FA supplementation in layer diets. No significant differences in laying performance and egg quality were found by LO addition compared with the CON group, which is consistent with a previous study (Forte et al, 2016). The dietary inclusion of NFA and FA significantly increased the egg weight.…”
Section: Discussionsupporting
confidence: 92%
“…Probiotics are also well-studied feed additives, with reported benefits on laying performance, egg quality, and immune response of laying hens (Zhang et al, 2012;Forte et al, 2016;Abd et al, 2017;Mazanko et al, 2018). Lactobacillus plantarum is one of the most common probiotic strains, and possesses strong antioxidant and antimicrobial activities (Tsai et al, 2012;Niu et al, 2018).…”
Section: Comparison Of the Dietary Supplementation Of Lactobacillus Pmentioning
confidence: 99%
“…Guo, Dong, Liu, and Tong () found that dietary supplementation with BS did not significantly influence on the egg production, egg weight and feed intake of 28‐week‐old Hy‐Line laying hens. Forte et al () reported that the effects of supplementation with 0.1% Lactobacillus acidophilus and 0.05% BS on the performance of 16‐week‐old Hy‐Line laying hens and found no differences among the different groups. We assumed that the variation in the results of the aforementioned studies can be ascribed to several factors, including the dose of Bacillus species, the age of the animals, feed form, diet composition and hygiene status.…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor is nutrition. Several nutrients have an influence on the production of antibodies because they provide essential elements for the immune response (Du et al, 2016;Forte et al, 2016;Perween et al, 2016). One of the most important factors for the production of antibodies is the use of adjuvants.…”
Section: Resultsmentioning
confidence: 99%